2008
DOI: 10.1038/ejhg.2008.215
|View full text |Cite
|
Sign up to set email alerts
|

MET and autism susceptibility: family and case–control studies

Abstract: Autism is a common, severe and highly heritable neurodevelopmental disorder. The International Molecular Genetic Study of Autism Consortium (IMGSAC) genome screen for linkage in affected sib-pair families identified a chromosome 7q susceptibility locus (AUTS1), that has subsequently shown evidence of increased sharing in several independent multiplex samples and in two meta-analyses. Taking into account the location of the MET gene under this linkage peak, and the fact that it has recently been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 53 publications
5
77
0
1
Order By: Relevance
“…Sousa et al report association of a potential functional variant of the MET gene with autism in two patient samples. 1 These results increase to five the cohorts in which variants of the MET gene are reported to be associated with autism, suggesting that the MET receptor tyrosine kinase and the molecular cascade through which it signals contribute to autism risk.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Sousa et al report association of a potential functional variant of the MET gene with autism in two patient samples. 1 These results increase to five the cohorts in which variants of the MET gene are reported to be associated with autism, suggesting that the MET receptor tyrosine kinase and the molecular cascade through which it signals contribute to autism risk.…”
mentioning
confidence: 68%
“…5 The results of Sousa et al failed to replicate genetic association of the rs1858830 C allele, but identified association of another allele with a similar potential to regulate the expression of the MET gene. 1 1 Although direct evidence to indicate function of the rs38845 A allele is not presented, Sousa et al 1 discuss in silico evidence that the A allele creates a binding site for the transcription factor IRF1, and present a hypothesis of how the A allele may contribute to decreased MET protein expression in individuals with autism. In addition to the SNP alleles that may regulate transcription, rare de novo copy number variation losses of the chromosomal region including the MET gene have also been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogene MET is also strongly linked to ASD etiology, having been supported by a number of studies in the past decade (e.g. IMGSAC, 2001;Campbell et al, 2006Campbell et al, , 2008Sousa et al, 2009). Recently, Eagleson et al (2011) reported a role for Met signaling in cortical interneuron development in vitro in a mouse model.…”
Section: Replicated Common Variants From Candidate Gene Studiesmentioning
confidence: 81%
“…Chromosome 7q also contains the MET gene, located at 7q31 [59], as well as HGF, located at 7q21.1 [60]. Several MET variants have been shown to increase risk for ASDs [61][62][63][64][65][66]. One SNP in particular, rs1858830, has been found to be associated with the co-occurrence of autism with gastrointestinal conditions [63].…”
Section: Genetic Association Of Autism With the Met Signaling Pathwaymentioning
confidence: 99%